2017
DOI: 10.1177/1469787417735609
|View full text |Cite
|
Sign up to set email alerts
|

Identifying predictors of students’ perception of and engagement with assessment feedback

Abstract: Higher education students' perception of and level of engagement with the feedback they receive has gained increasing attention in the literature to identify areas which require educators' attention. However, predictors of students' perception and engagement have yet to be identified. To address this, a survey measuring students' views and practices regarding feedback was completed. Characteristics of the individual student (gender, age and whether English is their first language) the learning environment (stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Using qualitative case studies, Han and Hyland (2015) demonstrated that students differ in the extent to which they accept or resist feedback, and in their emotional reactions. In a survey, Ali, Ahmed, and Rose (2018) explored whether characteristics of the student (i.e., gender, age, and whether English was their first language), the learning environment (whether students lived on/off campus), and the programme of study (year and second subject) predicted students' self-reported engagement with feedback. The only significant predictor was year of study, with engagement declining over successive years of the programme.…”
Section: Psychological Approaches To Feedbackmentioning
confidence: 99%
“…Using qualitative case studies, Han and Hyland (2015) demonstrated that students differ in the extent to which they accept or resist feedback, and in their emotional reactions. In a survey, Ali, Ahmed, and Rose (2018) explored whether characteristics of the student (i.e., gender, age, and whether English was their first language), the learning environment (whether students lived on/off campus), and the programme of study (year and second subject) predicted students' self-reported engagement with feedback. The only significant predictor was year of study, with engagement declining over successive years of the programme.…”
Section: Psychological Approaches To Feedbackmentioning
confidence: 99%
“…Wilson, 2007 cited in Li andLindsey, 2015). Ali et al (2017) and Li and Lindsey (2015) show that such vagueness is a reflection of lecturers' perceptions of criteria and the subsequent learning impasse where neither lecturers nor students fully understand the link between assignments and assessment criteria. Many lecturers, therefore, add some written comments for the student (i.e.…”
Section: Rubric-referenced Assessmentmentioning
confidence: 99%
“…First, the framework of Hattie and Timperley is one of the few which explicitly includes feedforward (Boud and Molloy, 2013b;Hounsell et al, 2008;Sadler, 1989) as a category which is relevant considering the function of rubrics suggested in the literature (cf. Ali et al, 2017). Second, the framework is well known in higher education.…”
Section: Scoring Modelmentioning
confidence: 99%
“…Lack of objective and timely feedback is a problem in developing student's hand skill and clinical judgement 3 . Additionally, it is advantageous that students receive consistent, unbiased and accurate feedback regarding their preclinical work 2,4,5 . Adjuvant methods such as tutors and digital media have shown to be effective in improving the preclinical learning process 6,7 .…”
Section: Introductionmentioning
confidence: 99%